Projeto constituinte de 1988 na era da austeridade fiscal: conciliação impossível - Nunes, Glauton Rogis Silva (2021)
This work aims to reflect on the 1988 constituent project aimed at the economic and social area, materialized in the text of the 1988 Federal Constitution, and its (in) compatibility with fiscal austerity policies, with reference to EC nº 95 / 2016, which instituted a new tax regime in the country and imposed individual limits on primary government expenditure for a period of 20 (twenty) years. Using a qualitative and exploratory methodology, in a critical approach and using the bibliographic type of research, the role of the State in the economy will be analyzed in the light of its fundamental objectives. Firstly, the objectives, foundations, instruments and limits of state intervention under the Social State paradigm are studied. Then, the issue of fiscal austerity, its origins, concept, fundamentals and its current application in the country is addressed, whose reflections point to a Neoliberal State project, which has the greatest distinction in the defense of the “Minimum State”. In view of this situation, EC nº 95/2016 is being studied as the institution of a permanent austerity economic policy, its concrete effects on social policies and social well-being, in order, in the end, to conclude that the defense of fiscal austerity as the only one response to sustainable economic development and fiscal responsibility, is nothing more than a fallacious discourse that seeks to sabotage the Constitution and the emancipatory project of the country to serve the interests of big capital, above all, the financial, which profits from the interest on the Brazilian public debt.